Predisposing Factors of Leukorrhea and Its Impact on Students in the Health Vocational Studies Program at Bengkulu University - Asmara, Citra; Dewiani, Kurnia; Purnama, Yetti; Asmariyah; Yulyani, Linda (Journal of Health Sciences and Medical Development, 2023)
Leukorrhea, a common health concern among women, has been the subject of this research, which sought to identify the underlying predisposing factors contributing to its occurrence. A sample of 90 students from the Health Vocational Study Program at Bengkulu University was purposively selected through an observational approach. The research examined several independent variables, including Knowledge, Personal Hygiene, and Stress, while focusing on leukorrhea as the dependent variable. Employing the Chi-Square test and regression analysis, the findings revealed a lack of significant association between knowledge and leukorrhea. In contrast, a substantial relationship was established between personal hygiene behavior and stress about leukorrhea. Multivariate analysis indicated that individual hygiene behavior emerged as the most influential factor affecting leukorrhea. This study highlights the significant impact of personal hygiene behavior and stress on the occurrence of leukorrhea among students at Bengkulu University. Furthermore, it underscores the critical role of private hygiene practices in managing and preventing leukorrhea.